The architecture of public park : fading the line between architecture and landscape - Ahmad, Mohd. Hamdan (Fakulti Alam Bina, UTM, 2006)
This paper reviews 3 consultancy projects of public parks in nature. The projects were completed within the last 5 years by group of academic staffs in the faculty. Public Park design can be considered as design in the in-between territory. It hinges on the interdisciplinary relationship between two major fields, architecture and landscape architecture. Landscape architect from department of landscape architecture deals with the park and architect from the department of architecture normally deals with the related buildings. Other consultant from the faculty staff is quantity surveyor from department of quantity surveying, making Public Park as truly the most interdisciplinary project reflecting the multidisciplinary nature of the faculty of built environment. The projects being reviewed here illustrate how academic staffs can contribute to the community through consultancy, and by so doing reflects the good relationship between the university, the city and the public.